Cover Feature: Synthesis and Reactivity of Bis(silylene)‐Coordinated Calcium and Divalent Lanthanide Complexes (Chem. Eur. J. 65/2020). Issue 65 (6th October 2020) - Sun, Xiaofei; Simler, Thomas; Reiter, Kevin; Weigend, Florian; Roesky, Peter W.
Abstract : Divalent europium, ytterbium and calcium complexes coordinated by a chelating pyridine‐based bis(silylene) ligand (left in the cover image) were synthesized. Further reactions led to metal complexes ligated by a unique silylene‐pyridyl‐amido ligand (right in the cover image). More information can be found in the Full Paper by P. W. Roesky et al. on page 14888 .